Literature on website evaluation in health sector - Sarantis, Demetrios (2017)
A critical element in the evolution of health sector services provided through the internet is the development of appropriate websites that adequately serve the patients' needs. Hospitals, in order to deliver superior online services must first understand and then satisfy users’ expectations. Health sector website assessment is built on identifying underlying dimensions, and conceptualizing relative metrics. Research and practitioner interest in health sector website assessment has considerably risen in recent years. In this article aspects of relative academic studies in health sector website assessment are reviewed and a holistic health sector websites’ assessment framework is proposed, defining criteria and their relative indicators.